2019
DOI: 10.1002/ange.201904883
|View full text |Cite
|
Sign up to set email alerts
|

Pentacoordinated Al3+‐Stabilized Active Pd Structures on Al2O3‐Coated Palladium Catalysts for Methane Combustion

Abstract: Supported Pd catalysts are active in catalyzing the highly exothermic methane combustion reaction but tend to be deactivated owing to local hyperthermal environments. Herein we report an effective approach to stabilize Pd/SiO2 catalysts with porous Al2O3 overlayers coated by atomic layer deposition (ALD). 27Al magic angle spinning NMR analysis showed that Al2O3 overlayers on Pd particles coated by the ALD method are rich in pentacoordinated Al3+ sites capable of strongly interacting with adjacent surface PdOx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Such palladium active sites were introduced into the reaction sequence by postulating the presence of oxygen vacancies; oxygen vacancies are regenerated at the end of a catalytic cycle by recombination of surface hydroxyl groups formed in C-H bond activation steps, which allows explaining the negative reaction order of water (equation 1). Recently, PdO x and Pd-PdO x structures were also found on Al 2 O 3decorated Pd/SiO 2 catalysts synthesized by means of atomic layer deposition 22 .…”
Section: Introductionmentioning
confidence: 94%
“…Such palladium active sites were introduced into the reaction sequence by postulating the presence of oxygen vacancies; oxygen vacancies are regenerated at the end of a catalytic cycle by recombination of surface hydroxyl groups formed in C-H bond activation steps, which allows explaining the negative reaction order of water (equation 1). Recently, PdO x and Pd-PdO x structures were also found on Al 2 O 3decorated Pd/SiO 2 catalysts synthesized by means of atomic layer deposition 22 .…”
Section: Introductionmentioning
confidence: 94%
“…Ag, Pt, and Pd) to improve their catalytic activity and stability. [11][12][13] Besides, theoretical calculations have suggested that Al V species could promote BAS formation in ASAs as typically proposed for Al IV . 14 Therefore, increasing the Al V concentration in alumina and ASAs is promising for both enhancing surface Lewis acidity and Brønsted acidity, thereby overcoming the limitations of current efforts in tuning the concentration of Al IV and Al VI species.…”
Section: Introductionmentioning
confidence: 77%
“…This is consistent with DFT calculations which show that a surface oxide is more active than bulk PdO nanoparticles 17,18 . However, when Pd based catalysts are used for methane combustion, the metal Pd nanoparticle transforms to PdO, leading to the decrease in catalytic activity 19 . A well-known approach for improving the stability and reactivity of Pd based catalysts is to add Pt, which stabilizes the Pd phase in a metallic state by forming bimetallic PtPd even under oxidizing conditions 20 , leading to enhanced resistance to adsorption of water molecules.…”
Section: Introductionmentioning
confidence: 99%